Why Is The Identification of Causative Agent of Nocardiosis Essential at The Species Level? - Masoud Keikha (Pasteur Institute of Iran, 2017)
[No Abstract] Nocardia is a genus of weakly gram-positive, filamentous, aerobic, relatively slow-growing and partially acid-fast bacteria. These bacteria are ubiquities in environmental resources such as water, soil, dust, decomposing animal feces, and vegetables. This group of bacteria can enter the human body through inhalation and traumatic cutaneous inoculation and cause Nocardia infections. There are various types of nocardiosis including pulmonary, brain, cutaneous, cutaneous-lymphatic, and ocular infections. These infections often occur in immunocompromised patients including organ transplant recipients, corticosteroid drugs consumers, human immunodeficiency virus (HIV) patients, cancerous and even healthy individuals.